Dimerisation, rhodium complex formation and rearrangements of N-heterocyclic carbenes of indazoles - Guan, Zong; Namyslo, Jan C.; Drafz, Martin H. H.; Nieger, Martin; Schmidt, Andreas (Beilstein Journal of Organic Chemistry, 2014)
Deprotonation of indazolium salts at low temperatures gives N-heterocyclic carbenes of indazoles (indazol-3-ylidenes) which can be trapped as rhodium complexes (X-ray analysis). In the absence of Rh, the indazol-3-ylidenes spontaneously dimerize under ring cleavage of one of the N,N-bonds and ring closure to an indazole–indole spiro compound which possesses an exocyclic imine group. The E/Z isomers of the imines can be separated by column chromatography when methanol is used as eluent. We present results of a single crystal X-ray analysis of one of the E-isomers, which equilibrate in solution as well as in the solid state. Heating of the indazole–indole spiro compounds results in the formation of quinazolines by a ring-cleavage/ring-closure sequence (X-ray analysis). Results of DFT calculations are presented.
Keywords: E/Z isomerism; indazol-3-ylidene; mesomeric betaine; pyrazole; quinazoline; Rh complex